2020
DOI: 10.4040/jkan.19203
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Staffing and Health Outcomes of Psychiatric Inpatients: A Secondary Analysis of National Health Insurance Claims Data

Abstract: Purpose: The present study investigated the association between nurse staffing and health outcomes among psychiatric inpatients in Korea by assessing National Health Insurance claims data. Methods: The dataset included 70,136 patients aged 19 years who were inpatients in psychiatric wards for at least two days in 2016 and treated for mental and behavioral disorders due to use of alcohol; schizophrenia, schizotypal and delusional disorders; and mood disorders across 453 hospitals. Nurse staffing levels were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…Because we operationally defined TMD in this study, defining TMD patient groups solely based on diagnosis would diminish the accuracy. However, because the diagnostic accuracy of the HIRA–NPS claims is on average about 70%, 45 it has little effect on our findings. Therefore, subsequent studies utilising claims data should pay close attention to diagnostic accuracy.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Because we operationally defined TMD in this study, defining TMD patient groups solely based on diagnosis would diminish the accuracy. However, because the diagnostic accuracy of the HIRA–NPS claims is on average about 70%, 45 it has little effect on our findings. Therefore, subsequent studies utilising claims data should pay close attention to diagnostic accuracy.…”
Section: Discussioncontrasting
confidence: 53%
“…It has been reported that diagnosis is more accurate for inpatients, severely ill patients and patients in general/tertiary hospitals than it is for outpatients, patients with frequently mild diseases and patients in clinics, respectively. 45 Furthermore, we used the data of patients who were assigned corresponding diagnostic codes. However, it is possible that the data set included patients who had been assigned an incorrect code or excluded patients due to misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Fukasawa et al (2018), however, found the opposite, that a higher number of nurses per 10 beds were associated with increased use of restraints (OR = 1.74 95% CI: 1.35‐2.24). In other studies, nurse–patient ratio was not associated with restraint use (Bak et al, 2015; Donat, 2003; Khalil et al, 2017; Park et al, 2020). Bak et al (2015) also found no relationship between restraints and use of substitute staff.…”
Section: Resultsmentioning
confidence: 77%
“…Firstly, we defined underlying health conditions using administrative claims data generated only when patients visited healthcare facilities. Although claims data can be useful for certain types of healthcare research, it is important to be aware of its limitations, including potential inaccuracies, lack of clinical detail, and incomplete information on patient outcomes [ 59 ]. Consequently, the prevalence in our study would be underestimated.…”
Section: Discussionmentioning
confidence: 99%